An apolipoprotein A-V gene SNP is associated with marked hypertriglyceridemia among Asian-American patients - Pullinger, Clive R. (American Society for Biochemistry and Molecular Biology, 2008)
Apolipoprotein A-V (apoA-V) is an important regulator of plasma levels of triglyceride (TG) in mice. In humans, APOA5 genetic variation is associated with TG in several populations. In this study, we determined the effects of the p.185Gly>Cys (c.553G>T; rs2075291) polymorphism on plasma TG levels in subjects of Chinese ancestry living in the United States and in a group of non-Chinese Asian ancestry. The frequency of the less common cysteine allele was 4-fold higher (15.1% vs. 3.7%) in Chinese high-TG subjects compared with a low-TG group (Chi-square = 20.2; P < 0.0001), corresponding with a 4.45 times higher risk of hypertriglyceridemia (95% confidence interval, 2.18–9.07; P < 0.001). These results were replicated in the non-Chinese Asians. Heterozygosity was associated, in the high-TG group, with a doubling of TG (P < 0.001), mainly VLDL TG (P = 0.014). All eleven TT homozygotes had severe hypertriglyceridemia, with mean TG of 2,292 ± 447 mg/dl. Compared with controls, carriers of the T allele had lower postheparin lipoprotein lipase activity but not hepatic lipase activity. In Asian populations, this common polymorphism can lead to profound adverse effects on lipoprotein profiles, with homozygosity accounting for a significant number of cases of severe hypertriglyceridemia. This specific apoA-V variant has a pronounced effect on TG metabolism, the mechanism of which remains to be elucidated.